Computational Logic in Multi-Agent Systems 10th International Workshop, CLIMA X, Hamburg, Germany, September 9-10, 2009, Revised Selected and Invited Papers - Dix, J<U+00fc>rgen.; Fisher, Michael.; Novk̀, Peter. (Lecture Notes in Computer Science,, 2010)
This book constitutes the thoroughly refereed and revised post-conference proceedings of the 10th International Workshop on Computational Logic for Multi-Agent Systems, CLIMA X, held in Hamburg, Germany, in September 2009 - co-located with MATES 2009, the 7th German conference on Multi-Agent System Technologies. The 9 full papers, presented together with one invited paper, were carefully selected and reviewed from 18 submissions. The topics covered are formal approaches and model checking, belief-desire-intention, answer set programming and (multi-)agent systems, and coordination and deliberation.